Correction to: The impact of patient advisors on healthcare outcomes: a systematic review - Anjana E. Sharma; Margae Knox; Victor L. Mleczko; J. Nwando Olayiwola (BMC, 2018)
Following publication of the original article [1], the authors reported that reference no. 4 be changed. The details of the correction are as follows: